2008
DOI: 10.1523/jneurosci.0106-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminal Mutant Huntingtin Associates with Mitochondria and Impairs Mitochondrial Trafficking

Abstract: Huntington's disease (HD) is caused by polyglutamine (polyQ) expansion in huntingtin (htt), a large (350 kDa) protein that localizes predominantly to the cytoplasm. Proteolytic cleavage of mutant htt yields polyQ-containing N-terminal fragments that are prone to misfolding and aggregation. Disease progression in HD transgenic models correlates with age-related accumulation of soluble and aggregated forms of N-terminal mutant htt fragments, suggesting that multiple forms of mutant htt are involved in the select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
289
1
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 363 publications
(324 citation statements)
references
References 45 publications
(74 reference statements)
20
289
1
5
Order By: Relevance
“…The biochemical interaction of N-terminal Htt fragments with mitochondria was previously demonstrated in HD knock-in mouse brain 46 and mutant Htt oligomers co-localize with mitochondrial proteins Mitochondrial dysfunction has been previously implicated in HD pathogenesis (reviewed in ref. 45), although the mechanism of Htt involvement is still elusive.…”
Section: Discussionmentioning
confidence: 98%
“…The biochemical interaction of N-terminal Htt fragments with mitochondria was previously demonstrated in HD knock-in mouse brain 46 and mutant Htt oligomers co-localize with mitochondrial proteins Mitochondrial dysfunction has been previously implicated in HD pathogenesis (reviewed in ref. 45), although the mechanism of Htt involvement is still elusive.…”
Section: Discussionmentioning
confidence: 98%
“…The age-related death of medium spiny GABAergic neurons of the striatum occurs in HD (52) and GABAergic Purkinje cells are significant targets for degeneration in the cerebellar ataxias (53). Recent studies have linked neuronal degeneration in HD to disrupted mitochondrial function (54). For example, exogenous CoQ is neuroprotective in mouse models of HD (55).…”
Section: Mitochondrial Morphogenesis Protein Drp-1 Is Required For Thementioning
confidence: 99%
“…76 mtHtt associated with mitochondria in a knock-in mouse model of HD, and inhibited mitochondrial trafficking in cultured neurons. 77 Song et al 78 also observed both increased fragmentation and decreased mobility of mitochondria in neurons expressing mtHtt, as well as a novel interaction between mtHtt and the fission-related protein Drp1 that led to an increase in the GTPase activity of Drp1. This increase in GTPase activity would give rise to increased fission.…”
Section: Neural Disease: a Role For Mitochondrial Turnover And Dynamicsmentioning
confidence: 95%